Readiness Requirements for Adopting Blockchain Technology in Marketing Healthcare Services: A Case Study of the United Arab Emirates" - ليتيم خالد (Finance and Business Economies Review, 2023)
The study aimed to identify the requirements for adopting Blockchain technology in UAE's healthcare system and evaluate its applicability based on a literature review of adopting technology in marketing healthcare services. The study highlights the importance of identifying stakeholders responsible for adopting new technology to create a framework for assessing readiness. The main requirements for assessing readiness for adopting Blockchain technology are motivation, participation, technology, and structural readiness. In the UAE context, stakeholder readiness is crucial for driving healthcare Blockchain initiatives. However, the main challenge facing healthcare companies is the lack of knowledge and awareness, with 63% of them unaware of industry 4.0 technologies, including Blockchain, and their relevance to their business operations.